TRADER'S BEHAVIOR IN DISPOSING OF GARBAGE (CASE STUDY OF SOLOK CITY PASAR RAYA AREA) - Agung Aprilian Putra; ded chandra (DEPARTEMEN GEOGRAFI FIS UNP, 2026)
Research objectives: 1) Knowing the socio and demographic of traders. 2) Traders' understanding of market hygiene regulations. 3) Availability of landfills. 4) The behavior of traders in disposing of garbage. This research is a type of quantitative descriptive research using percentage descriptive analysis techniques and cross tabulations using the chi square method. The results of this study: 1) Socio and demographic traders of Pasar Raya Kota Solok, who dominate are women with the type of food merchandise and age range 40-49 years. 2) Traders' understanding of market hygiene regulations, traders know about market hygiene regulations and will be subject to sanctions if they violate them. 3) Availability of trash cans, traders who have basket-shaped trash cans dominate. 4) The behavior of traders, most of the traders behave actively with open behavior in disposing of garbage.